NADA NUEVO EN LAS ELECCIONES DEL 30 DE OCTUBRE DE 2011 EN MEDELLÍN. - Korman, Hyman (La Sociología en sus Escenarios, 2012)
Abstract. The scenes that unfolded in the electoral competition also showed to some similarity but differences - Although like in the 2007, the polarization climate was a very present element, in October of the 2011 mass media surpassed this it with the open intervention of an important one extreme right journal, the irruption of municipal civil servants in the electoral fight. Secondly, the polarization was constituted not only in a mobilizing fort of citizens to the ballot boxes but also in a clasist defense of a conception of city and in this way also the sensation was increased of which not only it was in the fight two social and enterprise conceptions of city but two sectors very defined. Elect mayor Gaviria won where he had to win: Communes of high social estratification like the candidate Perez in communes of low social estratification. What weighed in the fight was a sly dirty war that led an important one rightist mass media, the open participation in policy of officials government and the irruption of a third candidate supported by ex- president Uribe. Resumen.Los escenarios que se desplegaron en la competencia electoral mostraron algunas similitud pero también diferencias - Si bien al igual que en el 2007, el clima de polarización fue un elemento muy presente, en octubre del 2011 este lo superó con la abierta intervención de un importante medio de comunicación ultra conservador, la irrupción de funcionarios municipales en la contienda electoral. Segundo, la polarización se constituyó no sólo en un fuerte movilizador de ciudadanos a las urnas sino también en una defensa clasista de una concepción de ciudad y con ello también se incrementó la sensación de que no solo estaba en la pelea dos concepciones de ciudad sino dos sectores sociales y empresariales muy definidos. El alcalde electo Gaviria ganó adonde tenía que ganar: Comunas de estratos altos al igual que el candidato Pérez en comunas de estratos bajos. Lo que pesó en la contienda fue una solapada guerra sucia que lideró un importante medio de comunicación conservador, la abierta participación en política de funcionarios públicos y la irrupción de un tercer candidato apoyado por el ex presidente Uribe.